Scintillation Scanning of Lungs in Preoperative Assessment of Carcinoma of Bronchus. Issue 5666 (9th August 1969) - Walker, R. H. Secker; Provan, J. L.
Abstract : Lung scans with the use of macroaggregated human serum albumin labelled with technetium-99m were carried out in 52 patients before thoracotomy. Forty-three patients had carcinoma of the bronchus. Tumours less than 2 cm. in diameter on the chest radiograph were not detected. Larger tumours showed defects in perfusion, ranging in size from the mass seen on the chest radiograph to almost absent perfusion of the entire lung. The extent of the defect in perfusion was closely related to involvement of the pulmonary vessels at the hilum by distortion, compression, or invasion by the tumour. Bronchial obstruction played a less important part in producing the defects. The larger the defect in perfusion the greater was the involvement of the hilar and mediastinal structures and the more extensive was the surgery required. When perfusion of the affected lung was less than one-third of the total the tumour was found to be unresectable.